2020
DOI: 10.3390/antiox9100919
|View full text |Cite
|
Sign up to set email alerts
|

Memory-Enhancing Effects of Origanum majorana Essential Oil in an Alzheimer’s Amyloid beta1-42 Rat Model: A Molecular and Behavioral Study

Abstract: Origanum L. (Lamiaceae) is an important genus of medicinal and aromatic plants used in traditional medicine since ancient times as culinary herbs and remedies. The aim of the present study was to evaluate the chemical composition, as well as the biochemical and cellular activities of freshly prepared Origanum majorana L. essential oil (OmEO) in an Alzheimer’s disease (AD) amyloid beta1-42 (Aβ1-42) rat model. OmEO (1% and 3%) was inhaled for 21 consecutive days, while Aβ1-42 was administered intracerebroventric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 89 publications
(93 reference statements)
3
13
0
Order By: Relevance
“…In our previous study, we performed Y-maze test to verify whether the locomotor activity is affected by Aβ infusion (Lim et al, 2018). According to many studies, Y-maze and open field tests are the most commonly used tests for locomotor activity of rodents by counting the number of entries to the maze arms (Yamada et al, 1999;Zhang et al, 2015;Heredia-López et al, 2016;Postu et al, 2020). Our results showed that Aβ-injected group was not differ from any other groups in total entry number of Y-maze test.…”
Section: Effects Of Eefe On Cognitive Deficit In Aβ-injected Micesupporting
confidence: 46%
“…In our previous study, we performed Y-maze test to verify whether the locomotor activity is affected by Aβ infusion (Lim et al, 2018). According to many studies, Y-maze and open field tests are the most commonly used tests for locomotor activity of rodents by counting the number of entries to the maze arms (Yamada et al, 1999;Zhang et al, 2015;Heredia-López et al, 2016;Postu et al, 2020). Our results showed that Aβ-injected group was not differ from any other groups in total entry number of Y-maze test.…”
Section: Effects Of Eefe On Cognitive Deficit In Aβ-injected Micesupporting
confidence: 46%
“…Likewise, studies have revealed that oregano extract consumption improves learning and memory in normal rats, possibly owing to its antioxidant activity and inhibition of acetylcholinesterase (Ghaderi et al., 2020 ; Sheibani et al., 2011 ). In addition, the essential oil extracted from oregano has been shown to ameliorate cognitive dysfunction in Alzheimer's rats (Postu et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…route has been used to establish the amyloid-beta feature of AD. Through stereotaxic surgery, 50 rats received 4 μL of Aβ1-42 suspension (1 mM, Sigma-Aldrich, Darmstadt, Germany) in the third cerebral ventricle via a well-established, previously described protocol [ 66 ]. The remaining 10 rats, corresponding to the sham group, received the same volume of saline following the same protocol.…”
Section: Methodsmentioning
confidence: 99%
“…The relative quantification of histone-associated DNA fragments was performed by using a cell death detection ELISA kit version 8 (Roche Diagnostics, Mannheim, Germany) as previously described [ 66 ]. The wells were first coated with antibodies directed against DNA and histone, and then the amygdala protein extracts were added.…”
Section: Methodsmentioning
confidence: 99%